Platelet aggregation and antibacterial effects of an L-amino acid oxidase purified from Bothrops alternatus snake venom - Stabeli, R. G.; Marcussi, S.; Carlos, G. B.; Pietro, RCLR; Selistre-De-Araujo, H. S.; Giglio, JR; Oliveira, E. B.; Soares, A. M. (Elsevier B.V., 2004)
The isolation and biochemical/enzymatic characterization of an L-amino acid oxidase, Balt-LAAO-I, from Bothrops alternates snake venom, is described. Balt-LAAO-I is an acidic glycoprotein, pI similar to 5.37, homodimeric, M-r similar to 123, 000, whose Nterminal sequence is ADVRNPLE EFRETDYEVL. It displays a high specificity toward hydrophobic and basic amino acids, while deglycosylation does not alter its enzymatic activity. Bait-LAAO-I induces platelet aggregation and shows bactericidal activity against Escherichia coli and Staphylococcus aureus. In addition, this enzyme is slightly hemorrhagic and induces edema in the mouse paw. Bait-LAAO-I is a multifunctional enzyme with promising relevant biotechnological and medical applications. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: snake venom; L-amino acid oxidase; Bothrops alternatus; bactericidal effect; platelet aggregation; biotechnological application